Chill factor - Robinson, James G.; Johnson, Hugh; Warner Bros. Pictures (California : Warner Bros. Pictures, 1999)
'Most likey to succeed.' They're the least likely words you'll find below old yearbook photos of ice cream deliveryman and a convenience-store clerk. But now this loose-fitting due must succeed at any cost. A dying scientist has plopped into their hands a bioweapon canister code-named Elvis and told them to speed it to a military base. Buckle up, fellas. The same assassins who dealt the scientist his deathblow will do anything to Elvis
Executive producer, Jonathan A. Zimbert ; editor, Pamela Power
Cast: Cuba Gooding, Jr., Skeet Ulrich
Keywords: Suspense in motion pictures; Adventure films